Los tribunales administrativos en la materia de contratación pública - Romero-Pérez, Jorge Enrique (2014)
Administrative courts in the matters of government contracting have been established in response to criteria of legality, transparency, equality and development of the competence. The regulation on go- vernment contracting must be enforced, in the event of conflict, dispute or debate, by jurists qualified in this matter.